Discovery of neuroprotective agents that inhibit human prolyl hydroxylase PHD2. (15th May 2021) - Richardson, Nicole L.; O'Malley, Laura J.; Weissberger, Daniel; Tumber, Anthony; Schofield, Christopher J.; Griffith, Renate; Jones, Nicole M.; Hunter, Luke
Graphical abstract: Abstract: Prolyl hydroxylase (PHD) enzymes play a critical role in the cellular responses to hypoxia through their regulation of the hypoxia inducible factor α (HIF-α) transcription factors. PHD inhibitors show promise for the treatment of diseases including anaemia, cardiovascular disease and stroke. In this work, a pharmacophore-based virtual high throughput screen was used to identify novel potential inhibitors of human PHD2. Two moderately potent new inhibitors were discovered, with IC50 values of 4 μM and 23 μM respectively. Cell-based studies demonstrate that these compounds exhibit protective activity in neuroblastoma cells, suggesting that they have the potential to be developed into clinically useful neuroprotective agents.